Effect of Different Environments on the Properties of Polyamide Netting Materials. - Sandipan Mondal (KUFOS, 2018)
Abstract- Quality of the materials and their durability in any environmental condition are two important factors for the construction of a fishing gear. A knowledge on the material degradation is very useful for taking the preventive measures in proper time. The study aimed to find the changes in the properties and role of microbial loads in polyamide monofilament and multifilament samples kept in soil, water and weather for a period of 90 days. To assess the changes in properties tensile strength and weight loss of the samples were measured periodically throughout the study period. Load of microbes and their morphological characteristics were also observed and measured. It was found that multifilament samples had the more strength loss and percentage in weight loss than monofilament samples in the all three environments. It was also concluded that microbial loads had an effect on both mono and multifilament samples kept in soil and water but no direct effect on the samples kept in atmosphere by using correlation equation. Statistical analysis was done to find out the significant difference in the tensile strength and percentage of weight loss between and within the environments.